Neurodevelopment in normocephalic children with and without prenatal Zika virus exposure. Issue 3 (3rd September 2021) - Blackmon, Karen; Evans, Roberta; Fernandes, Michelle; Landon, Barbara; Noel, Trevor; Macpherson, Calum; Cudjoe, Nikita; Burgen, Kemi S; Punch, Bianca; Krystosik, Amy; Grossi-Soyster, Elysse N; LaBeaud, Angelle Desiree; et al.
Abstract : Objective: Zika virus (ZIKV) targets neural stem cells in the developing brain. However, the majority of ZIKV-exposed children are born without apparent neurological manifestations. It remains unclear if these children were protected from ZIKV neurotropism or if they harbour subtle pathology that is disruptive to brain development. We assess this by comparing neurodevelopmental outcomes in normocephalic ZIKV-exposed children relative to a parallel control group of unexposed controls. Design: Cohort study. Setting: Public health centres in Grenada, West Indies. Patients: 384 mother–child pairs were enrolled during a period of active ZIKV transmission (April 2016–March 2017) and prospectively followed up to 30 months. Child exposure status was based on laboratory assessment of prenatal and postnatal maternal serum. Main outcome measures: The INTERGROWTH-21st Neurodevelopment Assessment (INTER-NDA) package and Cardiff Vision Tests, administered and scored by research staff masked to child's exposure status. Results: A total of 131 normocephalic ZIKV exposed (n=68) and unexposed (n=63) children were assessed between 22 and 30 months of age. Approximately half of these children completed vision testing. There were no group differences in sociodemographics. Deficits in visual acuity (31%) and contrast sensitivity (23%) were apparent in the ZIKV-exposed infants in the absence of cognitive, motor, language or behavioural delays. Conclusions: Overall neurodevelopment is likely to be unaffected in ZIKV-exposed children with normal head circumference at birth and normal head growth in the first 2 years of life. However, the visual system may be selectively vulnerable, which indicates the need for vision testing by 3 years of age. Abstract : A follow up study of infants born to mothers with pregnancy exposure to Zika virus showed infants who had been exposed to Zika virus but who had a normal head circumference had overall normal development, but all such Zika virus infants should undergo formal visual testing.